Clove Flower Extract (Syzygium aromaticum) enhance Wound Healing Time, Bacterial Count, and IL 10 Levels in Methicillin Resistant Staphylococcus aureus infected Rats - Muttaqien, Rizal Arief,; Lestari, Endang Sri; Prajoko, Yan Wisnu; Susilaningsih, Neni (Diponegoro International Medical Journal, 2024)
To determine the effect of clove flower extract on the healing time of incision wounds, bacterial count and IL-10 levels in rats infected with MRSA.Method. Experimental study with a post-test-only control group design in rats that were given incisions on their backs. Random allocation was carried out to divide the Sprague Dawley rats into 6 groups (@5 rats). Healing time was assessed based on the length of days, the bacterial count was examined from the blood and then counted by culture using nutrient agar. IL-10 levels were examined from the venous blood of rats and then measured using an ELISA kit assessed by a certified microbiologist. Data were analyzed and processed using the One Way Anova - Post Hoc hypothesis test.Results. The bacterial count in the clove flower extract group was lower than the group without antibiotics and there was no difference compared to the group given antibiotics. IL-10 levels in the group given clove flower extract were lower when compared to the group given antibiotics. The wound healing time in the clove flower extract group was faster when compared to the group with or without antibiotics.Conclusion. Clove flower extract enhancewound healing in MRSA-infected rats.